Ensino e aprendizagem da produção textual no ensino médio: um estudo de caso - Monica Moreira de Magalhaes (2016)
This research is an ethnographic based case study. It aims to investigate a singular and historically situated reality, concerning the teaching-learning writing process, even though it projects to wider contexts which involve the issue. The nature of this study is, essentially, qualitative, centered on description and analysis of data. The elements under investigation are the writing teaching process developed by two Portuguese teachers and the learning process undergone by 45 students from two classes, enrolled in the third year in High School in a state public school, in the interior of Minas Gerais. The main purpose of the research is to investigate the reality of the writing teaching and learning processes in this context in order to analyze the data and discuss possibilities to improve teaching. As intervention activities, students wrote texts which were read, corrected and evaluated by the researcher, based on the Matrix of Reference to Writing for ENEM 2014. The results obtained indicate that there is the necessity of a systematized planning to teach writing. It is necessary to plan concrete objectives for the writing teaching. Teachers need to have more pedagogical support and mechanisms which can ensure them a higher self-esteem, security and confidence in their work in classroom. Students, on their hand, as responsible for what they write, also need self-esteem. They need to believe more in their potential to writing, because only by this way they will be able to properly take on the authorship in their texts. It is expected that discussions of this work can positively impact teacher continuing education and, consequently, students formation concerning higher proficiency in writing.